Bilateral ureteral triplication: A case report - Wahyudi, Irfan (Urol Case Rep, 2020)
Ureteral triplication is among the rarest congenital disorder of the urinary tract. A review of the literature has shown that only about one hundred cases have been reported worldwide. The reports on bilateral ureteral triplication cases, however, are extremely scarce. A female infant was presented with a history of recurrent febrile UTI since birth. Computed tomography urography scan revealed bilateral ureteral triplication. Combination of contrast studies and endoscopic procedure were utilized to establish the diagnosis. Management for this anomaly varies from conservative to interventional surgery. This patient underwent laparoscopic left ureteroneocystostomy and ureteral tailoring.